Mechanical Analysis of Locally Developed Hand-Pushed Vibratory Soil Compactor for Usage Acceptability - Akinnuli, Basil Olufemi; Mogaji, Pius Bamidele; Esan, Ayodeji Joseph (European Journal of Scientific Exploration, 2018)
The developed machine was designed by the authors to have a chassis mass of 32.68 kg, water reservoir of 6.57 x 10-3 m3, the discharge rate for soil wetting is 3.49 x 10-3 m3 s-1, and compacting rate of the vibrator is 5000 vpm with a power of 4.08 KW (5.5HP). The machine chassis was analyzed using solid works tools. The actual chassis model information is: mass 30.78 kg, volume 0.003921 m3, density of 7850 kg/m3 and weight is 301.647 N. The material properties are: Name (1023 Carbon Steel sheet), Yield strength (2.82685 x 108 N/m2), Tensile strength (4.25 x 108 N/m2), Elastic modulus (2.05 x 1011 N/m2), Poisson’s ratio (0.29), Mass density (7850 kg/m3), Shear modulus (8 x 1010 N/m2) and Thermal expansion coefficient (1.2 x 10-5 Kelvin). The maximum allowable stress and strain that the vibrator seat could be subjected to are 958,428,688 N/m2 and 2.983 x 106 respectively. Stress and strain above these will cause the failure of the seat.